1.) Write using negative exponents 1/6^4
2.)Multiply and simplify 3^2(negative 2)X3^3
3.)Divide and simplify 4^2/4^4
4.)Divide and simplify y/y5
5.)Simplify (2^3)^2
6.)Solve 2.3=y/2
2.)Multiply and simplify 3^2(negative 2)X3^3
3.)Divide and simplify 4^2/4^4
4.)Divide and simplify y/y5
5.)Simplify (2^3)^2
6.)Solve 2.3=y/2

Negative exponent means that it is shifted to the bottom.
1) this is simply 6^(4)
when you multiply things with different powers but the same base number, you add the powers
2)3^(2)*3^3=>3^(32)=>3^1=3, so the answer is 3
when you divide you do the opposite, you subtract
3)4^(24)=>4^(6)=>1/4^6
4)pretty sure you can't simplify any more, but I could be wrong on this one.
When raising powers to powers, you multiply them (I'm assuming that's supposed to be ^(2))
5)2^(3*2)=>2^6=1/2^6
6)multiply by 2 to both sides
4.6=y
1) this is simply 6^(4)
when you multiply things with different powers but the same base number, you add the powers
2)3^(2)*3^3=>3^(32)=>3^1=3, so the answer is 3
when you divide you do the opposite, you subtract
3)4^(24)=>4^(6)=>1/4^6
4)pretty sure you can't simplify any more, but I could be wrong on this one.
When raising powers to powers, you multiply them (I'm assuming that's supposed to be ^(2))
5)2^(3*2)=>2^6=1/2^6
6)multiply by 2 to both sides
4.6=y

1) 6^4 (negative four)
a negative power will shift something to the other side of a fraction
2) 3^3/3^2
again, the negative power 'moves' the number to the other side of the fraction
3^1
the three cubed cancels the three squared from the bottom, leaving only the three to the power of one (3)
3) 1/(4^6)
again with the neagtive index. i think this is the main point you need to understand from this
4) I do not believe this can be further simplified
5) 2^ 6
(a^m)^n = a^(m*n)
6) y=4.6
multiply both sides by 2, and then divide both sides by 1
hope this helped
a negative power will shift something to the other side of a fraction
2) 3^3/3^2
again, the negative power 'moves' the number to the other side of the fraction
3^1
the three cubed cancels the three squared from the bottom, leaving only the three to the power of one (3)
3) 1/(4^6)
again with the neagtive index. i think this is the main point you need to understand from this
4) I do not believe this can be further simplified
5) 2^ 6
(a^m)^n = a^(m*n)
6) y=4.6
multiply both sides by 2, and then divide both sides by 1
hope this helped

any number raised to a negative exponent is equal to 1 over the number with its positive exponent. example: 5^ 2 = 1/5²
1. 1/6^4 = 6^ 4
2. 3^ 2 x³ = x³/3² or x³/9
3. 4^2/4^4 = 1/4^6
4. y/(y5) is already in its simplified form
5. if it's (2³)^2 then (2³)^ 2= 1/(2³)² = 1/2^6 or 1/128
6. 2[2.3= y/2]2 >multiply both sides by 2 to eliminate denominator
4.6 = y >then divide both sides by 1 to get y
y= 4.6
1. 1/6^4 = 6^ 4
2. 3^ 2 x³ = x³/3² or x³/9
3. 4^2/4^4 = 1/4^6
4. y/(y5) is already in its simplified form
5. if it's (2³)^2 then (2³)^ 2= 1/(2³)² = 1/2^6 or 1/128
6. 2[2.3= y/2]2 >multiply both sides by 2 to eliminate denominator
4.6 = y >then divide both sides by 1 to get y
y= 4.6

1. 6^4
2. 3^1 = 3.
3. 1/4^6
4. Already simplified.
5. 2^6, 64.
6. 4.6 = y
2. 3^1 = 3.
3. 1/4^6
4. Already simplified.
5. 2^6, 64.
6. 4.6 = y

1. 6^4
2. 3
3 1/4^6 or 4^6
4 y^6
5 1/64
6 6=y/2 y=12
2. 3
3 1/4^6 or 4^6
4 y^6
5 1/64
6 6=y/2 y=12